Determination of Approaches to the Epidemiological Surveillance of Intraamniotic Infection of the Fetus - M. D. Zlokazov; A. V. Lyubimova; L. A. Ivanova; I. S. Bazaeva; T. V. Os'mirko; А. G. Komissarov (Эпидемиология и вакцинопрофилактика, 2020)
In recent years, there has been a steady increase in the number of infections specific to the perinatal period, wth 60% of the perinatal infections in St. Petersburg being intra-amniotic infections (IAI) of the fetus.The aim of the study is to identify the frequency and risk factors of Intra-amniotic infection of fetus, not elsewhere classified (ICD-10 code P39.2).Materials and methods. The study, conducted in a maternity hospital in St. Petersburg, included 240 newborns wth clinically established diagnoses from the P39 group «Other infections specific to the perinatal period».Results of the study. A definition of the case of IAI of the fetus, not elsewhere classified (ICD-10 code P39.2), was proposed - the presence of IAI signs in the histological study of the placenta and the presence of a systemic inflammatory response in a newborn child. Using the definition of a confirmed case the frequency of fetal IAI was 0.42 per 100 children live-born, which is 3.5 times lower than the frequency of clinically determined diagnoses. Risk factors for the confirmed case were: asymptomatic bacteriuria, pyelonephritis, colpitis, tonsilltis, cervical erosion in the history of cervical anamnesis, cardiovascular diseases in the mother.Conclusion. In the course of epidemiological surveillance of intra-amniotic infection of the fetus, it is necessary to use the definition of the case with further stratification of data on the newborn's body weight at birth. In order to reduce the incidence of this pathology, it is necessary to develop programs aimed at identifying and eliminating factors that increase the risk of maternal and fetal IAI.